Breast thermography - Laviña, Raúl; Mate, Miguel; Albo, Manuel; Pérez Penco, Ernesto; Pressa, Carlos; del Campo, Alberto (Cirugía del Uruguay, 1983)
lnitial impressions about 105 mamary termography, performed in CEN .DI.MA Of the Asociación Española 1 a. de socorros Mutuos, are analized. The few number of cases do not pretend to give additional information to that analized by reknowns authors, but allows to place sorne definited types of mamary tumors and its value.